MEWUJUDKAN PARTISIPASI MASYARAKAT UNTUK PENINGKATAN PEMBANGUNAN DESA - Khotami, Khotami (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2016)
Participation is a participation or involvement of a person (individual or community members) in a particular activity. Participation is often associated with development activities. Development is also interpreted as a change to the better. While terms such participation would be clearer if the meaning is directly linked with the development of its own motion. Thus it is related to the growing awareness of the villagers so that they are motivated to make changes actively and towards a better direction. Development activities in rural areas are often faced with the problem of low quality of human resources in rural areas are mostly low-skilled, also including those involved in the administration of the village administration. It also relates to the dynamics of an ever-changing society. Therefore, it is necessary to urge and innovation to realize participation as a step to achieve an increase in rural development by having human capital, structural capital as leadership and supporting components to realize the participation of rural communities. So from that cultivated positive steps to foster community participation in development. To foster the participation of the need for encouragement and innovation as the capital in order to achieve the desired objectives, among others, include capital human capital, leadership capital and structural capital, so that between the government and society occurred harmonious cooperation in realizing the goals of rural development. Therefore, the participation from the community village itself is desirable in order to succeed role in the development of the village.